Formulation and Evaluation for Solid Lipid Microparticles of Efonidipine - Pethappachetty, Palanisamy; Chandira, Rajappa Margret; Rajandhran, Meenaa; Samy, Dominic Antony (Asian Journal of Biological and Life Sciences)
Design a dosing frequency level for efonidipine and examine its pharmacokinetics and dynamics. Solid Lipid Microparticles were made using efonidipine. ATR-FTIR research 4000 to 400cm-1, SEM analysis, Diffrantional Scanning Calorimetry, Power X-ray diffraction. The current state of in vitro drug release research is discussed. Then we’ll look at the ingredients and procedures for making solid lipid microparticles. It is possible to prepare and use microparticles in many ways. Hypotensive solid lipid microparticles with efonidipine showed promise. They all survived three months at 4°C. Oral administration is the most usual technique. Many pharmacological dosage forms are intended to delay drug release. Its systemic circulation and plasma profile are prolonged.
Keywords: Efonidipine; Glyceryl Trilaurate and Egg lecithin; Solid Lipid Microparticles; Stearic acid